Plasma and Intracellular Antiretroviral Concentrations in HIV-Infected Patients under Short Cycles of Antiretroviral Therapy - Zehnacker, Laura; Abe, Emuri; Mathez, Dominique; Alvarez, Jean-Claude; Leibowitch, Jacques; Azoulay, Stéphane (AIDS Research and Treatment, 2014)
Study of plasma and intracellular concentrations of atazanavir, lopinavir, nevirapine, and efavirenz was conducted on 48 patients under short cycles of antiretroviral therapy. Intracellular concentrations (IC) were still measurable for all drugs after 85 h or 110 h drug intake despite the absence of drug in plasma for atazanavir and lopinavir. A linear relationship between plasma and intracellular efavirenz was observed. Further studies to fully understand the impact of IC in the intermittent antiviral treatment are required.